Emotion Regulation and Forgiveness among Female Inmates - Dwike Samata Sukmasari; Naomi Soetikno (Philanthropy: Journal of Psychology, 2024)
Female prisoners face various challenges during detention, including the loss of their roles as mothers, social isolation, and privacy restrictions. During detention, female prisoners may feel bored, fear violence, and have difficulty building trust. They need to engage in emotion regulation and forgiveness to maintain their mental health. Sometimes, female prisoners experience difficulties in emotion regulation. Previous research has indicated that difficulties in emotion regulation impact the forgiveness process. This study aims to examine the relationship between emotion regulation and forgiveness among female prisoners. The research method used is quantitative with a convenience sampling technique. A total of 190 female prisoners aged 18-65 years completed the Difficulties in Emotion Regulation Short Form (DERS-SF) and Heartland Forgiveness Scale (HFS) questionnaires. Spearman Correlation Analysis yielded r = -.324 and p = .001 < .01. The results indicate a negative and significant relationship between difficulties in emotion regulation and forgiveness. This means that the stronger the difficulties in emotion regulation, the weaker the tendency toward forgiveness. This conclusion can also be interpreted to mean that there is a positive and significant relationship between emotion regulation and forgiveness. In other words, the stronger the ability in emotion regulation, the stronger the tendency toward forgiveness. The research findings are expected to provide important insights into the development of more effective interventions to support emotion regulation and forgiveness, as well as the social reintegration process of female prisoners. Additionally, these findings can serve as a foundation for the development of further research ideas to explore the factors that influence emotion regulation and forgiveness. Keywords: Correctional Institutions; Emotion Regulation; Female Inmates; Forgiveness; Prison